(untitled) (Malaysian Management Journal, 2013)
Entrepreneurial activities are important factors in creating and increasing employment opportunities and fuelling economic growth. Entrepreneurship is an important source of job creation and opening career opportunities for both women and men. However, women are less likely to have successful enterprises or businesses than men. This paper is aimed at assessing women entrepreneurship in Nigeria: their present state of involvement in comparison to the male entrepreneurs, their challenges, contributions and performance in the formal and informal business sector of the economy. The paper employed the descriptive method of analysis. An inductive methodology involving observation, collection of secondary data and the analysis of such data was employed. To this end, a lot was devoted to the presentation and analysis of data obtained from the Small and Medium Enterprise Development Agency of Nigeria, the National Bureau of Statistics and the Federal Office of Statistics. It was discovered that women participate more in the micro business (informal sector) constituting 42.1% of the ownership structure. Their performance constitutes 13.57% in the formal sector as against the male entrepreneurs at 86.43%. Their poor performance and contribution are a result of the constraints they face. It was also discovered that their performance was higher in the Trade and Agricultural Sector in 1997 but higher in the Education and Service Sector by 2012. Among others, it is recommended that good practice in supporting women entrepreneurship should be initiated by the government in the form of training courses, advisory services or creating awareness campaigns.